DIAGNÓSTICO DA ATUAÇÃO DO MÉDICO VETERINÁRIO COMO FONTE DE INFORMAÇÃO PARA TUTORES DE CÃES E GATOS EM XX XX/XX - Soares, Judiele; Rocha, Thaís Gomes [UNESP]; Langoni, Hélio; Campagnol, Daniela; dos Santos Honsho, Cristiane (Universidade Federal do Tocantins, 2025)
The increased interaction between humans and animals in new family arrangements has highlighted the role of veterinarians as sources of information. In addition to preventing zoonoses, proper veterinary guidance impacts the maintenance of animal health and well-being as well as that of their human contacts. The objective of this study was to assess the role of veterinarians as sources of information regarding the well-being and health of pets through a questionnaire administered to pet owners at XX of XX in the municipality of XX/XX. The majority of pet owners were female (66%), aged between 42 and 50 years (50%), and had higher levels of education: high school, undergraduate, and postgraduate (86%). Of the animal population in this study, 65.8% were dogs and 12.7% were cats, predominantly adults and neutered. Seventy-eight percent are considered family members, and more than half cohabit with the owner’s residence. Concerning veterinary care, most pet owners maintain vaccination schedules and control ecto- and endoparasites; however, they visit veterinarians only when their pets are ill. Most animals are fed twice daily, with food selection based on veterinary recommendations or the food's composition/quality. Additionally, daily physical activity is provided. Owners possess considerable knowledge regarding spaying/neutering and obesity in animals; however, some gaps remain that need to be addressed by veterinarians to reduce misconceptions that directly impact animal health.